The canonical structure of Podolsky's generalized electrodynamics on the null-plane - Bertin, M. C.; Pimentel, B. M. [UNESP]; Zambrano, G. E. R. (American Institute of Physics (AIP), 2011)
In this work, we analyze the canonical structure of Podolsky's generalized electrodynamics on the null-plane. We show that the constraint structure presents a set of second-class constraints, which are exclusive of the analysis on the null-plane, and an expected set of first-class ones. An inspection on the field equations leads to the generalized radiation gauge on the null-plane. Dirac Brackets are then introduced by considering the problem of uniqueness under the chosen initial-boundary conditions of the theory. (C) 2011 American Institute of Physics. [doi: 10.1063/1.3653510]
Keywords: electrodynamics